The struggles of indian immigrants in establishing a home in Malaya in K.S. Maniam’s, in a far country (1993) and M. Kumaaran’s, Semmannum Neela Malargalum (1971) - Mani, Manimangai; Veeraputhran, Veeramohan (Center for Resource, Research and Publication Services, 2017)
The coming of British to Malaya and the opening of rubber plantations, in the late 19th century, paved way for many people from India who were looking for a better life. To many Indians especially the Southerners, coming to Malaya was an escapism from the dire poverty that hit India at that time. Little did they know the struggle that they will have to go through in establishing a new home in a foreign land. This paper will probe into the struggles of these immigrants in Malaya during the pre and post independence years. This study will be based on the novels of two popular Indian writers, K.S. Maniam and M. Kumaaran. Maniam’s, In a far Country (1993) and Kumaaran’s, Semmannum Neela Malargalum (1971) which is written in Tamil, depict on the painful journey encountered by the immigrants and their descendents. They had to wade through displacement, frustration, poverty, rejection and caste system in order to establish a home in the new land. This paper will discuss the journey of these characters to become part of Malaya and how acquiring of land and education is seen as the only way of establishing a sense of belonging to this new place called home.